2020
DOI: 10.1186/s13054-020-03155-3
|View full text |Cite
|
Sign up to set email alerts
|

Automated vs. conventional ventilation in the ICU: a randomized controlled crossover trial comparing blood oxygen saturation during daily nursing procedures (I-NURSING)

Abstract: Background: Hypoxia is common during daily nursing procedures (DNPs) routinely performed on mechanically ventilated patients. The impact of automated ventilation on the incidence and severity of blood oxygen desaturation during DNPs remains unknown. Methods: A prospective randomized controlled crossover trial was carried out in a French intensive care unit to compare blood oxygen pulse saturation (SpO 2) during DNPs performed on patients mechanically ventilated in automated and conventional ventilation modes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 30 publications
(52 reference statements)
1
26
0
Order By: Relevance
“…The search identified a total of 801 studies; after removal of duplicates and screening for eligibility, 45 studies in adult 13–57 and six studies in paediatric patients 58–63 were considered for this analysis (Fig. 1 and eTable S1, http://links.lww.com/EJA/A926).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search identified a total of 801 studies; after removal of duplicates and screening for eligibility, 45 studies in adult 13–57 and six studies in paediatric patients 58–63 were considered for this analysis (Fig. 1 and eTable S1, http://links.lww.com/EJA/A926).…”
Section: Resultsmentioning
confidence: 99%
“…1 and eTable S1, http://links.lww.com/EJA/A926). Thirty-five studies had a parallel randomised design 13–19,21,23,25–31,33,34,36,38–40,43–57,62,63 ; 12 had a crossover randomised design 20,22,24,32,35,37,41,42,58–61 . Only five studies were multicentre investigations 23,33,36,38,39 .…”
Section: Resultsmentioning
confidence: 99%
“…The surgical position of patients after anesthesia may have a particular impact on ventilation. [ 12 ] Some surgical positions may restrict thoracic or diaphragm movement or increase lung blood volume due to liquid gravity, resulting in decreased thoracic and lung compliance, tidal volume, and lung capacity. Shoulder arthroscopic surgery is mainly performed in lateral decubitus, and ventilation is significantly reduced in patients with a low-prone head, lateral decubitus, and lumbar pad.…”
Section: Discussionmentioning
confidence: 99%
“…In some situations in the ICU, such as during daily nursing procedures, it can be challenging to maintain adequate oxygenation and patients are at risk of having low SpO2 that goes unrecognized. A randomized crossover study in a large number of ICU patients showed that INTELLiVENT-ASV was able to reduce the incidence and severity of blood oxygen desaturation during daily nursing procedures as compared to nonautomated ventilation [33 ▪ ].…”
Section: Closed-loop Control Of Oxygenationmentioning
confidence: 99%